Finance and Development, March 1974. (Finance and Development; Finance and Development, 1974)
This paper highlights that the distribution of income and wealth in developing countries has become a matter of great concern to all those interested in development. The paper highlights that in Latin America, the poorest half of the population receives about the same share of income as the top 1 percent and the lowest 70-75 percent of the population the same share as the top 5 percent. It is clear that the distribution of income and wealth will have substantial implications for the pattern of consumption and production in developing countries.